Evaluation of the effectiveness of a South African laboratory cryptococcal antigen screening programme using a retrospective cohort and a cluster-randomised trial design. Issue 8 (5th August 2022) - DeSanto, Daniel J; Bangdiwala, Ananta S; Van Schalkwyk, Erika; Skipper, Caleb P; Greene, Greg; Paxton, Juliet; Huppler Hullsiek, Kathy; Mashau, Rudzani; Rajasingham, Radha; Boulware, David R; Govender, Nelesh P
Abstract : Introduction: Cryptococcal meningitis is a common fungal opportunistic infection and a leading cause of death among people with advanced HIV disease in sub-Saharan Africa. The WHO recommends cryptococcal antigen (CrAg) screening followed by pre-emptive therapy to prevent cryptococcal meningitis and death in this population. In 2016, South Africa was the first country to implement reflexive laboratory CrAg screening nationally. The Cryptococcal Antigen Screen-and-Treat National Evaluation Team (CAST-NET) aims to evaluate the effectiveness of this national screening programme to optimise health outcomes. Methods and analysis: The CAST-NET study consists of two integrated parts: a retrospective cohort study and a cluster-randomised trial (CRT). The retrospective cohort study will determine 6-month cryptococcal meningitis-free survival among CrAg-positive patients. Secondary outcomes include the proportion of CrAg-positive results noted for action in the CrAg-positive patient chart, the proportion of CrAg-positive patients offered and accept/decline a lumbar puncture, the proportion of CrAg-positive patients prescribed antifungal therapy and the proportion of CrAg-positive patients who have antiretroviral therapy initiated or reinitiated at an appropriate time according to South African national guidelines. Cohort data will be analysed by the type of facility (ie, hospital vs primary health clinic) at which the patient was diagnosed with antigenaemia. The CRT will determine if the appointment and mentoring of a healthcare worker, or 'crypto champion', at intervention facilities is associated with a higher proportion of CrAg-positive persons initiating pre-emptive fluconazole therapy. Secondary outcomes will include 6-month cryptococcal meningitis-free survival and the proportion prescribed fluconazole maintenance treatment. Ethics and dissemination: Ethics approvals were received from the University of the Witwatersrand Human Research Ethics Committee (Medical), the University of KwaZulu-Natal Biomedical Research Ethics Committee and the University of Pretoria Faculty of Health Sciences Research Ethics Committee. Study results will be disseminated to the South African Department of Health and participating facilities through peer-reviewed publications and reports.